Applications of 3D Maxillary Dental Arch Scanning for Mathematical Prediction of Orthodontic Treatment need for Complete Unilateral Cleft Lip and Palate Patients - Vasiliauskas, A.; Šidlauskas, A.; Šaferis, V.; Adaškevičius, R.; Linkevičienė, L. (Elektronika ir Elektrotechnika, 2010)
The aim of study was to determine the most informative morphological criteria of maxillary dental arch for mathematical prediction of orthodontic treatment need for complete unilateral cleft lip and palate patients. Study was based on examination of 40 patients (mean age 6.4±0.4 years) with congenital non-syndromic complete unilateral cleft lip and palate according to elaborated study plan. Measurements of maxillary diagnostic models of the studied subjects were performed in 3D computerized images. The three-dimensional scanner based on the laser triangulation method was used for scanning dental casts. Analysis of diagnostic models included assessment of length, width of dental arches and their relationship anteroposteriorly and transversally, height of palate and the shape of maxillary dental arch. Dental arch relationship anteroposteriorly was assessed according to 5 – Year-Old Index for complete unilateral cleft lip and palate patients. The analysis of occlusion and the form of maxillary dental arch was performed by assessment of the degree 36,3 mm 112 of posterior and anterior crossbite. Discriminant analysis was performed by using statistical analysis software SPSS 16. The length of maxillary dental arch altitude proved to be the most credible morphological criterion for evaluation of occlusion anteroposteriorly (77.1 percent prognostic value) in children with complete unilateral cleft lip and palate in order to predict orthodontic treatment need during the period of early mixed dentition. The width of maxillary dental arch in the area of second primary molars proved to be the most credible morphological criterion for evaluation of occlusion transversally (77.8 percent prognostic value) in children with complete unilateral cleft lip and palate in order to predict orthodontic treatment need during the period of mixed dentition. Long-term follow up is required in order to confirm effectiveness of cleft care. Ill. 6, bibl. 8, tabl. 4 (in English; abstracts in English, Russian and Lithuanian).